We are given the following system of equations:
![\begin{gathered} x+y=2,(1) \\ y=2x+5,(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/4asbd7de9p7g8gtd54lf7qk8z46plhovoo.png)
To solve this system we will use the method of substitution. We will replace the value of "y" from equation (2) into equation (1).
![x+2x+5=2](https://img.qammunity.org/2023/formulas/mathematics/college/lxbz29jr9mzewmk3o5m9fxgjjwooayoris.png)
Now we will add like terms:
![3x+5=2](https://img.qammunity.org/2023/formulas/mathematics/college/lvjx1y8eqz20v72lqww673i15jnlbyqoei.png)
Now we will subtract 5 to both sides of the equation:
![\begin{gathered} 3x+5-5=2-5 \\ 3x=-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/23kvdk7k5lnupftgimysekcj68l6zmkn74.png)
Now we will divide by 3:
![x=-(3)/(3)=-1](https://img.qammunity.org/2023/formulas/mathematics/college/6w0frsauo8k6bcd6olo53s85xsq5kw1o8y.png)
Now we will replace the value of "x" in equation (2):
![y=2(-1)+5](https://img.qammunity.org/2023/formulas/mathematics/college/pczppxjl5q8wysl4z05s6dkl38et2rapqm.png)
Solving the operations:
![\begin{gathered} y=-2+5 \\ y=3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/irflnjmr3cbw9g6lfeaulbugpt0keeho1s.png)
The solution of the system is:
![(x,y)=(-1,3)](https://img.qammunity.org/2023/formulas/mathematics/college/ga9kz02rw4jh9qyxu4yxlwo83muxdu01r0.png)